الحكم التعبدي في البحث الأصولي : دراسة تحليلية - يوسف، ما جان مينغ محمد (al-Jami'ah al-Islamiyah al-'Alamiyah bi- Maliziya, 2006)
This study concentrates on clarifying the reality of devotional rules in Islamic legislation in terms of their foundation and theory. It mentions both literal and SharīÑah definitions of the term, discusses opinions of some UÎūlī scholars about it, shows its relationship with some other UÎūlī terms, explains why the wise Lawgiver putts this kind of rules in His legislation. The study also mentions the distinguishing features of the devotional rules, their area in which they come, and their methods of identification. It also demonstrates the impact of disputes of jurists regarding devotionality of the rules in Islamic legislation in general, and in juridical matters in particular. The researcher mentions the opinions of UÎūlī scholars about the issue: what is the original status of the Islamic rules, are they devotional or rational? He presents the proofs of each opinion, discusses them to reach to the preferential view. After criticizing all opinions and pointing out their shortages, he concludes the preponderant one according to his view. The researcher follows three research methodologies in this study: induction, analysis and criticism. At the end of the study, the researcher reaches to his conclusions, one of them is that devotional rules have their own features which distinguish them from the rational rules; the other one is that calling to abolish the devotional rules, or to make all rules to be devotional, will lead to negative consequences for Islamic legislation, even if the caller’s motive is good. Lastly, it is sensible to put both devotional and rational rules in their right places, without abolishing or enlarging the first, which may lead to touch upon what nobody can know exactly in detail but Allah SubÍānahū Wa TaÑālā, or abolishing the second one to make all rules devotional, which may destroy the flexibility of legislation and its good response to continuously arising new issues and incidents.